Handbook on the physics and chemistry of rare earths. - Bunzli, Jean-Claude G.; Pecharsky, Vitalij K. (Handbook on the physics and chemistry of rare earths, 2015)
Handbook on the Physics and Chemistry of Rare Earths is an ongoing series covering all aspects of rare earth science-chemistry, life sciences, materials science, and physics. The main emphasis of the Handbook is on rare earth elements [Sc, Y and the lanthanides (La through Lu)] but information is also included, whenever relevant, on the closely related actinide elements. The individual chapters are comprehensive, broad, up-to-date critical reviews written by highly experienced invited experts. The series, which was started in 1978 by Professor Karl A. Gschneidner Jr.